LEGAL BASIS FOR TAKING THE LAND OWNED AND COMPENSATION FOR THE AFFECTED LAND - Maytsa Atika Al Maghfiroh; Fatma Ulfatun Najicha (UNTAG Law Review, 2021)
Indonesia always been active in carrying out development activities such as public development. The government has a duty to make Development for the public for the welfare of the people. The problem of land acquisition is considered vulnerable handling because it covers the lives of people. Currently, it is considered very difficult to carry out development for the public interest on state-owned land. The purpose of this research is to find out that the taking of rights to land due to the widening by the government of private land rights to realize national development have laws underlie it. The government compensation for freehold land taken from the community with an agreement that has been deliberated beforehand. The process of providing compensation must be balanced so that the owners of land rights are not harmed. In this research, the library research method is used by examining through books, journals, laws, and other written documents related to the issues to be discussed. The results showed that the process of taking over land rights due to widening by the government was based on Law Number 2 of 2012. The compensation provided is alsofurther explained in Presidential Regulation No. 65 of 2006.